Physical Activity among Adolescents in Urban and Rural Area in South Sulawesi, Indonesia: Exploring the Influence of Environmental Factors - Yusuf, Rezky Aulia; Muhsanah, Farihah; Cakke, Syiar; Amirah, Alya Dafa; Patimah, Sitti; Awalia, Nurul (Journal of Aafiyah Health Research (JAHR), 2022)
Abstrack Background: The neighborhood environment can affect the physical activity of adolescents, including the problem of the availability of sports or play facilities, sidewalks for pedestrians, fields, and environmental hygiene problems. The influence of the environment on physical activity (PA) in adolescents between urban and rural areas will have a different effect. Thes study purpose to explore environmental factors that influence adolescent’s participation in PA in the context of the urban and rural area environment. Method: Snowball sampling technique was used to get ten students from urban and rural areas respectively. Students aged 13 to 15 years were involved in the offline and online interview (by a videocall through WhatsApp) with semi-structured questions guidelines. Interview guidelines consisting of five-item topic questions and each topic has a different number of questions, with a total of 17 questions. This study also involved the photovoice procedures, such as photo-taking, selecting, contextualizing, and codifying themes. NVivo 12 software for qualitative data analysis. Results: The findings reveal that while adolescents in rural areas have access to natural resources such as hills and small woods, they are unaware of how to use these resources to promote and engage in PA. Poor natural resource management, a lack of awareness, a lack of sidewalk infrastructure, distance, road safety, and a lack of PA facilities were all issues that limited teenagers' participation in physical activity. Meanwhile, adolescents in urban area with abundant, safe, and clean facilities, as well as a diverse sports community were more likely to stay at home to play with the gadget. Conclusion: It is proposed that health promotion and physical activity instruction for teenagers in metropolitan areas is urgently needed, with a particular focus on limiting the use of gadgets and improving intervention-related safety. Basic amenities such as play places and pedestrian infrastructure are required in a rural region to promote adolescent PA. Any intervention should make use of natural resources, which are less expensive, environmentally friendly, and long-lasting.